The Influence of Celebrity Influencers and Brand Credibility on Consumer Purchase Intentions for The Brand: The Mediating Role of Attitudes Toward The Brand and Attitudes Toward Brand Credibility in The Case of Nadiraa Hijab - Bunga Rizqa Putri Laksono (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study examines the influence of celebrity influencers and brand credibility on consumer purchase intentions for the Nadiraa Hijab brand in Yogyakarta. The sample consisted of 380 female respondents aged 17-50 years who were seeking product information on social media. Data was collected through an online survey using a google form questionnaire. Data analysis was carried out using SmartPLS which includes classical assumption testing, instrument testing and hypothesis testing. The results of the study indicate that celebrity influencers and brand credibility have a direct impact on consumer purchase intentions and brand attitudes. Additionally, there is an indirect effect through brand attitude and brand credibility, which, although not direct, still contribute to consumer purchasing decisions.